Inkonstitusionalitas Peraturan Gubernur Jawa Barat Nomor : 12 Tahun 2011 tentang Larangan Kegiatan Jemaat Ahmadiyah Indonesia Di Jawa Barat - Mangunsong, Nurainun (UIN Sunan Kalijaga, 2014)
This writing studies on West Java Governor rule No. 12 /2011 on banning Ahmadis activities examined with Law No. 12/2011 and article 28 E and J 1945 amandement of constitution, Law No. 23/2014 jo Law No. 32/2004, Law No. 9/1999 on Human Rights, and Law No. 12/2005 on legalization of International Covenant On Civil And Political Rights. The result of this research showed that formally or materially the West Java Governor rule is not a good product of law and many contradiction in it.